Analisis Besaran Erosi dan Stabilitas Lereng dengan Perkuatan Soil Nailing - Balu, Rasyid; Patuti, Indriati Martha; Achmad, Fadly (Jurnal Teknik, 2025)
The Gorontalo Outer Ring Road (GORR), with a length of 45.3 km, is a road constructed by cutting through the foot of slopes, posing a potential risk of landslides. Land-use changes on the slopes have been utilized by local residents for agricultural purposes and tourist attractions. This, of course, can affect the stability of the slopes surrounding the road. Therefore, this study aims to determine the magnitude of erosion and slope stability along the Gorontalo Outer Ring Road. In this study, erosion analysis was conducted using the USLE (Universal Soil Loss Equation) method, while slope stability analysis – both natural and reinforced with soil nailing – was performed using the Bishop method with the aid of Geo5 software. Based on the research results, the erosion analysis using the USLE method found that the average erosion rate on the northern slope is 79.77 tons/year, while the average erosion rate on the southern slope is 25.27 tons/year. The slope safety factor analysis shows that the southern slope under seismic load has a safety factor (FK) of 0.78, while the northern slope under seismic load has a safety factor (FK) of 0.66. Slope safety factor analysis with soil nailing reveals that the southern slope under seismic load has a safety factor (FK) of 1.87, and the northern slope has a safety factor (FK) of 1.73. Based on the analysis results, the slopes meet the required standards, with FK > 1.11 in accordance with SNI 8460:2017.